Marine polysaccharide-based electromagnetic absorbing/shielding materials: design principles, structure, and properties. Issue 33 (8th August 2022) - Wang, Honghan; An, Qingda; Xiao, Zuoyi; Tong, Yao; Guo, Lin; Zhai, Shangru; Xiao, Ling-Ping; Ha, Chang-Sik
Abstract : An investigation of design principles, preparation processes and structural properties is carried out to predict the development tendency of marine polysaccharide-based electromagnetic response materials which cater to the current targeted demands. Abstract : Due to the urgent demand for electromagnetic (EM) response materials and intensive exploration by researchers, environment-friendly lightweight multifunctional electromagnetic wave (EMW) absorbing and electromagnetic interference (EMI) shielding materials have taken the centerstage, rather than just striving for high intensity. Marine polysaccharide (alginate, chitosan)-based EMW absorbing and EMI shielding materials that combine the advantages of biomass and aerogels play a "bridging" role in the design of dielectric/magnetic composites with appropriate conductivity, providing a superb platform for regulating the balance between the dielectric constant and permeability as well as achieving synergy between impedance matching and attenuation constants. By virtue of the fantastic properties of marine polysaccharide-based EM response materials, such as 3D structure, large specific surface area, high porosity, and self-doped heteroatoms, it is not only favorable to handle defect engineering for EM attenuation and construct heterostructures enriched in dipoles but also to endow the candidates with multifunctionality for practical potential through a facile preparation process. This review comprehensively introduces recent advancements in EM attenuation in marine polysaccharide-based EMW absorbing and EMI shielding materials as well as the feasible strategies, attenuation characteristics, and mechanisms. Furthermore, the challenges and prospects are also proposed to predict the development tendency of these EM response materials.